Creencias sobre la matemática de estudiantes de básica secundaria del liceo femenino mercedes Nariño y su relación con el logro académico Usme (2018)
Throughout this investigation an adaptation was made to the questionnaire on epistemological knowledge on Math taken from Annia Esther Vizcaino’s doctoral thesis with the aim of using it to determine the existing degree of knowledge about Math of Elementary and Middle school students, particularly those seventh, eighth and ninth-graders from a state all-girls school in Bogota.